2022
DOI: 10.1021/acs.inorgchem.2c00196
|View full text |Cite|
|
Sign up to set email alerts
|

Synthesis, Structure, and Luminescence of Mixed-Ligand Lanthanide Trifluoroacetates

Abstract: A series of new mixed-ligand lanthanide trifluoroacetates of formula Ln­(4-cpno)­(tfa)3(H2O)·H2O (Ln = Sm, Eu, Gd, Tb, Dy; 4-cpno = 4-cyanopyridine N-oxide; tfa = trifluoroacetate) is reported. Trifluoroacetates were synthesized as chemically pure polycrystalline solids and their crystal structures were probed using single-crystal and powder X-ray diffraction. Ln­(4-cpno)­(tfa)3(H2O)·H2O solids make up an isostructural series in which LnO8 polyhedra are bridged by 4-cpno to form edge-sharing dimers. Trifluoroa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Excitation of the host (336 nm) results in a much higher lanthanide emission than direct excitation of the Eu 3+ (395 nm, 5 L 6 ← 7 F 0 ), confirming an energy transfer process from STE to Eu 3+ ion (Figure S15). Such energy transfer further quenches the STE emission and leads to a low PLQY of 1.16% in Cs 2 AgEuCl 6 NCs, which is lower than other silver-lanthanide NCs.…”
Section: Resultsmentioning
confidence: 98%
“…Excitation of the host (336 nm) results in a much higher lanthanide emission than direct excitation of the Eu 3+ (395 nm, 5 L 6 ← 7 F 0 ), confirming an energy transfer process from STE to Eu 3+ ion (Figure S15). Such energy transfer further quenches the STE emission and leads to a low PLQY of 1.16% in Cs 2 AgEuCl 6 NCs, which is lower than other silver-lanthanide NCs.…”
Section: Resultsmentioning
confidence: 98%
“…[13][14][15] They also are used for the mild oxidation of alkanes, [16] alkenes, [17] alkynes, [18][19][20] amides, [21] difluorocarbene, [22] silyl enol ethers, [23] ynamides, [24] and water. [25] In coordination chemistry, azine-N-oxides are utilized as ligands for the preparation of transition metal complexes manifested catalytic, [26,27] therapiutic, [28,29] luminescent, [30] and magnetic properties. [31][32][33] Moreover, many azine-N-oxides have valuable properties themselves.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, when it comes to their light-emitting properties, only a handful of studies have been reported. [14][15][16][17][18][19][20][21] These reports probed the room-temperature photoluminescence of Ln(tfa) 3 (H 2 O) 3 as a means of elucidating structural details 14,[16][17][18] or of understanding the impact of organic sensitizers on lanthanide emission. 15,[19][20][21] The temperature dependence of the luminescence response of these materials has not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17][18][19][20][21] These reports probed the room-temperature photoluminescence of Ln(tfa) 3 (H 2 O) 3 as a means of elucidating structural details 14,[16][17][18] or of understanding the impact of organic sensitizers on lanthanide emission. 15,[19][20][21] The temperature dependence of the luminescence response of these materials has not been studied. This is remarkable considering the widespread interest in identifying hybrid organic-inorganic platforms amenable to the design of lanthanide-based luminescent thermometers.…”
Section: Introductionmentioning
confidence: 99%